PENGARUH BAURAN PEMASARAN, PSIKOLOGIS, DAN FAKTOR LINGKUNGAN TERHADAP KEPUTUSAN WISATAWAN MENGUNJUNGI OBYEK WISATA MASJID AGUNG JAWA TENGAH - Harsanti, Khurita Desi; Farida, Naili; Saryadi, Saryadi (Jurnal Ilmu Administrasi Bisnis, 2014)
One of the attractions in Semarang is Masjid Agung Jawa Tengah. This study aims to determine whether there is influence between Marketing Mix (X1), Psychology (X2), and Environmental Factors (X3) to the Decision Travelers (Y). The type of this research is explanatory research, data collection techniques are using interviews and data collection devices using a questionnaire with a sample of 100 respondents who are traveling to Masjid Agung Jawa Tengah through nonprobability sampling technique by using purposive sampling method. The analysis techniques using validity, reliability test, simple linear regression, multiple linear regression, T test and F test with SPSS tools 20.00. Results of statistical calculations with linear regression analysis are shown by the regression equation Y = 0.886 + 0.036 X1 + 0.184 X2 +0.149 X3. From the regression equation is known that the Marketing Mix, Psychology, and Environmental factors have an influence on the Travelling Decision. The calculations result of determination coefficient are 0.329 or 32,9 %. Based on the results of the data analysis we can conclude there are some the influence of Marketing Mix, Psychological, and Environmental Factors on Decision Travelers visiting Masjid Agung Jawa Tengah and has a strong degree of closeness of this relationship, it means the higher of Marketing Mix, Psychological, and Environmental Factors the higher the Travelers decision. The advice that given in this research aimsto improve the current Marketing Mix which is applied and optimizes the facility in Masjid Agung Jawa Tengah.Â